Sound analyses of a Japanese traditional stringed instrument of Okinawa: the shamisen - Hamdan, Sinin; Sinin, Aaliyawani E.; Said, Khairul A. M.; Musib, Ahmad F.; Duin, Ezra M. A. (North Carolina State University, 2025)
The shamisen is a three-stringed, plucked instrument that is used in a variety of genres, including folk music and kabuki theater. A PicoScope was used to obtain the signals from the shamisen. Open strings 1 and 2 exhibited discontinuities in the sequence of ascending notes. On string 1, B5 at fret 11 unexpectedly drops to C5 (instead of C6) at fret 12. On string 2, C6 at fret 17 drops to C♯5 (instead of C♯6) at fret 18. String 3 presented a continuous progression, ranging from C4 up to A5. The abrupt shifts from B5 to C5 and C6 to C♯5 on string 1 and 2 respectively results from the traditional Japanese approach to tuning (musicians emphasize relative intonation instead of conforming to equal-tempered pitch systems). Certain pitches may not hold functional significance within the melodic or harmonic framework, and their omission or alteration is consistent with historical performance practice. The variations in pitch captured in PicoScope data represent authentic outcomes of the shamisen’s culturally rooted tuning system and performance aesthetics. The PicoScope displayed the fundamental frequency one octave higher than the perceived pitch, while the gradient of the plotted partials frequency curves confirmed alignment with the actual sounding pitch.